2017
DOI: 10.1161/circheartfailure.117.004515
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of Fontan Failure

Abstract: Background Non-pulsatile pulmonary blood flow in Fontan circulation results in pulmonary vascular disease, but the potential relationships between pulmonary vascular resistance index (PVRI) and Fontan failure have not been studied. The objective was to determine whether the absence of subpulmonary ventricle in the Fontan circulation would make patients more vulnerable to even low-level elevations in PVRI, and that when coupled with low cardiac index (CI), this would identify patients at increased risk of Fonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…Finally, the thoracic IVC was replaced with a simulated Dacron shunt to mimic that typically implanted during the surgical procedure, [ 85,86 ] and pulmonary resistances were increased to model pulmonary hypertension, which is highly prevalent in Fontan patients. [ 87 ] The input parameters of this model and the schematic can be found in Table S2 and Figure S5 (Supporting Information), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the thoracic IVC was replaced with a simulated Dacron shunt to mimic that typically implanted during the surgical procedure, [ 85,86 ] and pulmonary resistances were increased to model pulmonary hypertension, which is highly prevalent in Fontan patients. [ 87 ] The input parameters of this model and the schematic can be found in Table S2 and Figure S5 (Supporting Information), respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 12 Published studies have variably used FCF as a composite endpoint to include death, transplantation or listing for transplantation. 11 , 13 Additionally, the development of patient‐experienced exercise intolerance, inability to carry out daily life activities and Fontan takedown have sometimes been included in the definition of FCF. 2 , 14 , 15 , 16 Other variables included within the spectrum of FCF were heart failure symptoms and other co‐morbidities including arrhythmias, thromboembolism, protein‐losing enteropathy (PLE), plastic bronchitis (PB), oedema, persistent effusions and liver dysfunction.…”
Section: Terms and Definitionsmentioning
confidence: 99%
“…Microvascular occlusion is common, as are arteriovenous malformations, leading to erroneous trans-pulmonary gradients. Although difficult to evaluate, elevated PVR is a key mechanism in FFP and unmasking can occur post-OHT following restoration of pulsatile flow with detrimental effects on right ventricular function (33,34). Early studies demonstrated higher post-transplant mortality with elevated © Annals of Cardiothoracic Surgery.…”
Section: Pulmonary Vascular Resistance (Pvr)mentioning
confidence: 99%